Degradability and clearance of inorganic nanoparticles for biomedical applications - Yang, Guangbao (2020)
Inorganic nanoparticles with tunable and diverse properties hold tremendous potential in the field of nanomedicine, while having non-negligible toxicity concerns in healthy tissues/organs that have resulted in their restricted clinical translation to date. In the past decade, the emergence of biodegradable or clearable inorganic nanoparticles has made it possible to completely solve this long-standing conundrum. A comprehensive understanding of the design of these inorganic nanoparticles with their metabolic performance in the body is of crucial importance to advance clinical trials and expand their biological applications in disease diagnosis. Here, a diverse variety of biodegradable or clearable inorganic nanoparticles regarding considerations of the size, morphology, surface chemistry, and doping strategy are highlighted. Their pharmacokinetics, pathways of metabolism in the body, and time required for excretion are discussed. Some inorganic materials intrinsically responsive to various conditions in the tumor microenvironment are also introduced. Finally, an overview of the encountered challenges is provided along with an outlook for applying these inorganic nanoparticles toward future clinical translations.